The inclusive story of disability and autism: the cases of the Speechless and Atypical TV series - Braga, Paolo (Medicina e Morale, 2020)
The article begins by sketching an overview of how cinema and TV fiction have historically misrepresented disability. Drawing on recent reports on US Television and on some influential contributions within Disability Studies, the piece highlights the enduring presence of two problems: a lack of representation, and, when the issue is tackled, the use of stereotypes. A new critical category is then taken into account âˆ’ «inspiration porn». Coined by disability rights advocates, it criticizes those cultural products where people with disabilities are diminishingly depicted with the only aim of giving people without disabilities the opportunity to feel positive emotions and fulfilment. Signs of change towards a more respectful representation of disability are perceivable in the international television offering, though. The article analyzes two recent TV series - Speechless and Atypical - which have tried to take a step forward the storytelling about inclusion. By focusing on ethical issues through the lenses of screenwriting theory, the analysis concentrates on two elements: how in the story the point of view of characters with disabilities and autism reveals their deep and rich interior life; how inclusion is presented to the audience as a feasible, motivating goal. In the light of the comparison of the two series, the article concludes by arguing that an ethical storytelling on disability should accomplish three general criteria: referential realism âˆ’ being informative âˆ’, optative realism âˆ’ a proactive take on drama âˆ’ and anthropological realism - give actions and relationships the right meaning to help the character accomplish himself/herself as a human being.